Prevalence and characteristics of sports injuries in athletes with flat feet: A quantitative descriptive study - Setiawan, Arif; Priyanto,; Yudhistira, Dewangga (Journal Sport Area, 2023)
The study of sports injuries is a crucial and captivating topic that requires thorough exploration. Understanding and effectively managing sports injuries is essential for coaches, instructors, and athletes. However, there is limited awareness among sports practitioners, particularly regarding flat foot conditions. Therefore, this research aims to identify common injuries among athletes with flat feet through a comprehensive survey. Employing a quantitative descriptive method with a survey-based approach. This study included a sample of 89 male athletes who sought treatment for sports-related injuries at massage clinics. Data collection techniques encompassed observations, interviews, questionnaires, and measurement tests. Purposive sampling was utilised for participant selection. Wet footprint tests, stature metres, weight scales, and questionnaires were employed for data collection. Data analysis employed the percentage formula and was supported by Excel software. The findings indicated that athletes with flat feet were more susceptible to knee injuries (69%), ankle injuries (31%), external causes of injury (22%), internal causes of injury (52%), and overuse injuries (26%). These results imply that athletes with flat feet who seek treatment at massage clinics commonly experience knee and ankle injuries, with internal trauma being the leading cause. This study contributes to a better understanding of injury identification among individuals with flat feet, aiding in the selection of appropriate sports activities. Limitations of this study include a single research site, an uneven distribution of sports disciplines, and a male-only sample. Future research should employ more comprehensive methods and ensure representative samples across various sports to facilitate proper generalisation of the data.